The effects of actor attractiveness and advertisement choice on mechanical avoidance behaviors - Nettelhorst, Stephen Charles (Kansas State University, 2013)
Two common types of advertisement avoidance behaviors in digital domains are skipping and zipping. Skipping involves pressing a “skip ad” button when viewing television content online, and zipping involves pressing a fast-forward button when viewing the same content through some type of recording device (e.g. Digital Video Recording device). The purpose of these studies was to examine if specific factors regarding the content of the advertisement, the persuasion context, and characteristics of the viewer reduce occurrences of skipping and zipping behavior. Participants in these two studies saw a combination of television shows and advertisements. One target advertisement marketed a fictional MP3 player while another discussed the dangers of binge drinking. One version each of the MP3 and binge drinking advertisements contained average-looking (i.e. normal) actors, and the other half contained above-average-looking (i.e. attractive) actors. Half of the viewers were allowed to choose which type of advertisements they would watch while the other half were forced to watch a particular type. The results of one study showed that participants were more likely to skip the MP3 advertisement than the binge drinking advertisement after making an advertisement choice when both contained normally attractive actors. These findings demonstrate that the effect of advertisement choice may be more complicated than previously found. Instead of acting as a means to improve avoidance rates, advertisement choice may make the content more salient to participants. Thus, viewers’ perceptions of the advertisement after making an advertisement choice may determine whether avoidance occurs.
Keywords: Advertisement avoidance; Advertisement choice; Actor attractiveness; Skipping; Zipping; Marketing (0338); Psychology (0621); Web Studies (0646)